Predictors of flu vaccination among urban Hispanic children and adults - Cohen, Bevin (2010)
BACKGROUND: Flu vaccination is effective for preventing infection, but coverage levels in the USA remain low—especially among racial/ethnic minorities. This study examines factors associated with flu vaccination in a predominantly Hispanic community in Manhattan, New York. METHODS: Households were recruited during the 2006–2007 and 2007–2008 flu seasons. Primary household respondents were interviewed to determine knowledge of flu transmission/treatment and vaccination status and demographic information for all household members. RESULTS: Vaccination coverage was 47.3% among children <5, 39.3% among 5–17-year-olds, 15.3% among 18–49-year-olds, 31.0% among 50–64-year-olds and 37.1% among adults ≥65 in year 1; and 53.1% among children <5, 43.6% among 5–17-year-olds, 19.5% among 18–49-year-olds, 34.1% among 50–64-year-olds and 34.3% among adults ≥65 in year 2. For children, younger age, having a chronic respiratory condition (eg, asthma), and greater primary respondent knowledge of flu were positively associated with vaccination. Among adults, female gender, older age, higher education, greater primary respondent knowledge of flu, having been born in the USA and having a chronic respiratory condition were positively associated with vaccination. The most common reasons cited for not being vaccinated were the beliefs that flu vaccination was unnecessary or ineffective. CONCLUSIONS: Possible methods for increasing vaccination levels in urban Hispanic communities include improving health literacy, making low-cost vaccination available and encouraging providers to use other office visits as opportunities to mention vaccination to patients. REGISTRATION NUMBER: This study is registered at http://ClinicalTrials.gov (NCT00448981).